Helicobacter pylori colonization of the adenotonsillar tissue : fact or fiction? - Vilarinho, Sérgio (2010)
Objective: The transmission of the gastric pathogen Helicobacter pylori involves the oral route. Molecular techniques have allowed the detection of H. pylori DNA in samples of the oral cavity, although culture of H. pylori from these type of samples has been sporadic. Studies have tried to demonstrate the presence of H. pylori in adenotonsillar tissue, with contradictory results. Our aim was to clarify whether the adenotonsillar tissue may constitute an extra gastric reservoir for H. pylori. Methods: Sixty-two children proposed for adenoidectomy or tonsillectomy were enrolled. A total of 101 surgical specimens, 55 adenoid and 46 tonsils, were obtained. Patients were characterized for the presence of anti-H. pylori antibodies by serology. On each surgical sample rapid urease test, immunohistochemistry, fluorescence in situ hybridization (FISH) with a peptide nucleic acid probe for H. pylori, and polymerase chain reaction–DNA hybridization assay (PCR–DEIA) directed to the vacA gene of H. pylori were performed. Results: Thirty-nine percent of the individuals had anti-H. pylori antibodies. Rapid urease test was positive in samples of three patients, all with positive serology. Immunohistochemistry was positive in samples of two patients, all with negative serology. All rapid urease test or immunohistochemistry positive cases were negative by FISH. All samples tested were negative when PCR–DEIA for H. pylori detection was used directly in adenotonsillar specimens. Conclusions: The adenotonsillar tissue does not constitute an extra gastric reservoir for H. pylori infection, at least a permanent one, in this population of children. Moreover, techniques currently used for detecting gastric H. pylori colonization are not adequate to evaluate infection of the adenotonsillar tissues.